Answer:
a) ![t = -\frac{ln(2)}{k}](https://tex.z-dn.net/?f=%20t%20%3D%20-%5Cfrac%7Bln%282%29%7D%7Bk%7D)
b) See the proof below
![A(t) = A_o 2^{-\frac{t}{T}}](https://tex.z-dn.net/?f=%20A%28t%29%20%3D%20A_o%202%5E%7B-%5Cfrac%7Bt%7D%7BT%7D%7D)
c) ![t = 3T \frac{ln(2)}{ln(2)}= 3T](https://tex.z-dn.net/?f=%20t%20%3D%203T%20%5Cfrac%7Bln%282%29%7D%7Bln%282%29%7D%3D%203T)
Explanation:
Part a
For this case we have the following differential equation:
![\frac{dA}{dt}= kA](https://tex.z-dn.net/?f=%20%5Cfrac%7BdA%7D%7Bdt%7D%3D%20kA)
With the initial condition ![A(0) = A_o](https://tex.z-dn.net/?f=%20A%280%29%20%3D%20A_o%20)
We can rewrite the differential equation like this:
![\frac{dA}{A} =k dt](https://tex.z-dn.net/?f=%20%5Cfrac%7BdA%7D%7BA%7D%20%3Dk%20dt)
And if we integrate both sides we got:
Where
is a constant. If we apply exponential for both sides we got:
![A = e^{kt} e^c = C e^{kt}](https://tex.z-dn.net/?f=%20A%20%3D%20e%5E%7Bkt%7D%20e%5Ec%20%3D%20C%20e%5E%7Bkt%7D)
Using the initial condition
we got:
![A_o = C](https://tex.z-dn.net/?f=%20A_o%20%3D%20C)
So then our solution for the differential equation is given by:
![A(t) = A_o e^{kt}](https://tex.z-dn.net/?f=%20A%28t%29%20%3D%20A_o%20e%5E%7Bkt%7D)
For the half life we know that we need to find the value of t for where we have
if we use this condition we have:
![\frac{1}{2} A_o = A_o e^{kt}](https://tex.z-dn.net/?f=%20%5Cfrac%7B1%7D%7B2%7D%20A_o%20%3D%20A_o%20e%5E%7Bkt%7D)
![\frac{1}{2} = e^{kt}](https://tex.z-dn.net/?f=%20%5Cfrac%7B1%7D%7B2%7D%20%3D%20e%5E%7Bkt%7D)
Applying natural log we have this:
![ln (\frac{1}{2}) = kt](https://tex.z-dn.net/?f=%20ln%20%28%5Cfrac%7B1%7D%7B2%7D%29%20%3D%20kt)
And then the value of t would be:
![t = \frac{ln (1/2)}{k}](https://tex.z-dn.net/?f=%20t%20%3D%20%5Cfrac%7Bln%20%281%2F2%29%7D%7Bk%7D)
And using the fact that
we have this:
![t = -\frac{ln(2)}{k}](https://tex.z-dn.net/?f=%20t%20%3D%20-%5Cfrac%7Bln%282%29%7D%7Bk%7D)
Part b
For this case we need to show that the solution on part a can be written as:
![A(t) = A_o 2^{-t/T}](https://tex.z-dn.net/?f=%20A%28t%29%20%3D%20A_o%202%5E%7B-t%2FT%7D)
For this case we have the following model:
![A(t) = A_o e^{kt}](https://tex.z-dn.net/?f=%20A%28t%29%20%3D%20A_o%20e%5E%7Bkt%7D)
If we replace the value of k obtained from part a we got:
![k = -\frac{ln(2)}{T}](https://tex.z-dn.net/?f=%20k%20%3D%20-%5Cfrac%7Bln%282%29%7D%7BT%7D)
![A(t) = A_o e^{-\frac{ln(2)}{T} t}](https://tex.z-dn.net/?f=%20A%28t%29%20%3D%20A_o%20e%5E%7B-%5Cfrac%7Bln%282%29%7D%7BT%7D%20t%7D)
And we can rewrite this expression like this:
![A(t) = A_o e^{ln(2) (-\frac{t}{T})}](https://tex.z-dn.net/?f=%20A%28t%29%20%3D%20A_o%20e%5E%7Bln%282%29%20%28-%5Cfrac%7Bt%7D%7BT%7D%29%7D)
And we can cancel the exponential with the natural log and we have this:
![A(t) = A_o 2^{-\frac{t}{T}}](https://tex.z-dn.net/?f=%20A%28t%29%20%3D%20A_o%202%5E%7B-%5Cfrac%7Bt%7D%7BT%7D%7D)
Part c
For this case we want to find the value of t when we have remaining ![\frac{A_o}{8}](https://tex.z-dn.net/?f=%20%5Cfrac%7BA_o%7D%7B8%7D)
So we can use the following equation:
![\frac{A_o}{8}= A_o 2^{-\frac{t}{T}}](https://tex.z-dn.net/?f=%20%5Cfrac%7BA_o%7D%7B8%7D%3D%20A_o%202%5E%7B-%5Cfrac%7Bt%7D%7BT%7D%7D)
Simplifying we got:
![\frac{1}{8} = 2^{-\frac{t}{T}}](https://tex.z-dn.net/?f=%20%5Cfrac%7B1%7D%7B8%7D%20%3D%202%5E%7B-%5Cfrac%7Bt%7D%7BT%7D%7D)
We can apply natural log on both sides and we got:
![ln(\frac{1}{8}) = -\frac{t}{T} ln(2)](https://tex.z-dn.net/?f=%20ln%28%5Cfrac%7B1%7D%7B8%7D%29%20%3D%20-%5Cfrac%7Bt%7D%7BT%7D%20ln%282%29)
And if we solve for t we got:
![t = T \frac{ln(8)}{ln(2)}](https://tex.z-dn.net/?f=%20t%20%3D%20T%20%5Cfrac%7Bln%288%29%7D%7Bln%282%29%7D)
We can rewrite this expression like this:
![t = T \frac{ln(2^3)}{ln(2)}](https://tex.z-dn.net/?f=%20t%20%3D%20T%20%5Cfrac%7Bln%282%5E3%29%7D%7Bln%282%29%7D)
Using properties of natural logs we got:
![t = 3T \frac{ln(2)}{ln(2)}= 3T](https://tex.z-dn.net/?f=%20t%20%3D%203T%20%5Cfrac%7Bln%282%29%7D%7Bln%282%29%7D%3D%203T)